Sympathetic Neural Adaptation to Hypocaloric Diet With or Without Exercise Training in Obese Metabolic Syndrome Subjects - Straznicky, Nora E.; Lambert, Elisabeth A.; Nestel, Paul J.; McGrane, Mariee T.; Dawood, Tye; Schlaich, Markus P.; Masuo, Kazuko; Eikelis, Nina; de Courten, Barbora; Mariani, Justin A.; Esler, Murray D.; Socratous, Florentia; et al. (Diabetes (New York, N.Y.), 2010)
Sympathetic Neural Adaptation to Hypocaloric Diet With or Without Exercise Training in Obese Metabolic Syndrome Subjects Nora E. Straznicky 1 , Elisabeth A. Lambert 1 , Paul J. Nestel 2 , Mariee T. McGrane 1 , Tye Dawood 1 , Markus P. Schlaich 3 , Kazuko Masuo 1 , Nina Eikelis 1 , Barbora de Courten 4 , Justin A. Mariani 5 , Murray D. Esler 1 , Florentia Socratous 3 , Reena Chopra 1 , Carolina I. Sari 1 , Eldho Paul 6 and Gavin W. Lambert 1 1 Human Neurotransmitters Laboratory, Baker IDI Heart & Diabetes Institute, Melbourne, Victoria, Australia; 2 Cardiovascular Nutrition Laboratory, Baker IDI Heart & Diabetes Institute, Melbourne, Victoria, Australia; 3 Neurovascular Hypertension and Kidney Disease Laboratory, Baker IDI Heart & Diabetes Institute, Melbourne, Victoria, Australia; 4 Clinical Physiology Laboratory, Baker IDI Heart & Diabetes Institute, Melbourne, Victoria, Australia; 5 Heart Failure Laboratory, Baker IDI Heart & Diabetes Institute, Melbourne, Victoria, Australia; 6 Department of Epidemiology and Preventive Medicine, Monash University, Melbourne, Victoria, Australia. Corresponding author: Nora E. Straznicky, nora.straznickyatbakeridi.edu.au . Abstract OBJECTIVE Sympathetic nervous system (SNS) overactivity contributes to the pathogenesis and target organ complications of obesity. This study was conducted to examine the effects of lifestyle interventions (weight loss alone or together with exercise) on SNS function. RESEARCH DESIGN AND METHODS Untreated men and women (mean age 55 ± 1 year; BMI 32.3 ± 0.5 kg/m 2 ) who fulfilled Adult Treatment Panel III metabolic syndrome criteria were randomly allocated to either dietary weight loss (WL, n = 20), dietary weight loss and moderate-intensity aerobic exercise (WL+EX, n = 20), or no treatment (control, n = 19). Whole-body norepinephrine kinetics, muscle sympathetic nerve activity by microneurography, baroreflex sensitivity, fitness (maximal oxygen consumption), metabolic, and anthropometric measurements were made at baseline and 12 weeks. RESULTS Body weight decreased by −7.1 ± 0.6 and −8.4 ± 1.0 kg in the WL and WL+EX groups, respectively (both P < 0.001). Fitness increased by 19 ± 4% ( P < 0.001) in the WL+EX group only. Resting SNS activity decreased similarly in the WL and WL+EX groups: norepinephrine spillover by −96 ± 30 and −101 ± 34 ng/min (both P < 0.01) and muscle sympathetic nerve activity by −12 ± 6 and −19 ± 4 bursts/100 heart beats, respectively (both P < 0.01), but remained unchanged in control subjects. Blood pressure, baroreflex sensitivity, and metabolic parameters improved significantly and similarly in the two lifestyle intervention groups. CONCLUSIONS The addition of moderate-intensity aerobic exercise training to a weight loss program does not confer additional benefits on resting SNS activity. This suggests that weight loss is the prime mover in sympathetic neural adaptation to a hypocaloric diet. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received June 28, 2009. Accepted October 4, 2009. © 2010 American Diabetes Association